Tumor associated macrophages support the growth of FGF9-induced lung adenocarcinoma by multiple mechanisms. (May 2018) - Hegab, Ahmed E.; Ozaki, Mari; Kagawa, Shizuko; Hamamoto, Junko; Yasuda, Hiroyuki; Naoki, Katsuhiko; Soejima, Kenzo; Yin, Yongjun; Kinoshita, Tomonari; Yaguchi, Tomonori; Kawakami, Yutaka; Ornitz, David M.; et al.
Highlights: TAMs dominate the immune response to the FGF9-induced adenocarcinoma. These TAMs are enriched for the alternatively activated (M2) macrophage subtype. These TAMs performed an immune suppressive function and promoted tumor growth. These TAMs induced fibroblast proliferation and angiogenesis. These TAMs overexpress Tgf-β, Vegf, Fgf2, Fgf10, Fgfr2 and matrix metalloproteinases. Abstract: Objectives: Tumor-associated macrophages (TAMs) are known to promote tumorigenesis but the mechanism(s) remain elusive. We have developed a mouse model of lung cancer that is initiated through an inducible overexpression of fibroblast growth factor 9 (FGF9) in type-2 pneumocytes. Expression of FGF9 in adult lungs resulted in a rapid development of multiple adenocarcinoma-like tumor nodules, and is associated with an intense immunological reaction. The purpose of this study is to characterize the immune response to the FGF9-induced lung adenocarcinoma and to determine the contribution of TAMs to growth and survival of these tumors. Materials and methods: We used flow cytometry, immunostaining, RT-PCR and in vitro culture system on various cell populations isolated from the FGF9-induced adenocarcinoma mouse lungs. Results: Immunostaining demonstrated that the majority of the inflammatory cells recruited to FGF9-induced lung tumors were macrophages. These TAMs were enriched for the alternatively activated (M2) macrophage subtype. TAMs performed a significantly high immune suppressive function on T-cells and displayed high levels of arginase-1 expression and activity. The growth and colony forming potential of tumor cells was induced by co-culture with TAMs. Additionally, TAMs were shown to promote fibroblast proliferation and angiogenesis. TAMs had high expression of Tgf-β, Vegf, Fgf2, Fgf10, Fgfr2 and several matrix metalloproteinases; factors that play multiple roles in supporting tumor growth, immune protection, fibroblast activation and angiogenesis. Conclusion: Our results provide evidence that the Fgf9 -induced lung adenocarcinoma is associated with recruitment and activation of M2-biased TAMs, which provided multiple means of support to the tumor. This model represents an excellent means to further study the complex interactions between TAMs, their related chemokines, and progression of lung adenocarcinoma, and adds further evidence to support the importance of TAMs in tumorigenesis.